Kadar Flavonoid Total dan Uji In Vitro Aktivitas Tabir Surya Ekstrak Kulit Batang Tuntun Angin (Elaeocarpus floribundus Blume) - Utami, Rahayu; Alpasiri, Ikhsan Mauludi; Fadhli, Haiyul; Ikhtiarudin, Ihsan; Mora, Enda; Furi, Mustika (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
The stembark of tuntun angin (Elaeocarpus floribundus Blume) has been traditionally using to treat various diseases, including fever, gingivitis and rheumatism. Our previous study has shown that stembark extract of this plant contains significant levels of total phenolics. The aim of this recent study was to determine total flavonoid content and providing an initial determination of sunscreen activity of n-hexane, ethyl acetate and methanol extracts of its stembark. Extraction was carried out by maceration method using three different solvents successively. The quantitative evaluation of total flavonoid content was expressed as mg Quercetin Equivalent (QE)/gram extract at a wavelength of 430 nm using a microplate reader. Evaluation of sunscreen activity was performed by determining value of Sun Protection Factor (SPF) using a UV-Vis spectrophotometer. The results showed that the n-hexane, ethyl acetate and methanol extracts contained total flavonoid levels of 9; 15.81 and 15.56 mgQE/g extract, respectively. Ethyl acetate extract showed the most potential sunscreen activity (ultraprotection category) among other extracts with SPF values of 44.626; 40,687; 33.710 and 23.607 for the tested concentrations of 1000; 800; 600 and 400 µg/mL, respectively. However, this activity is not as good as benzophenone-3 as positive control at a concentration of 50 μg/mL with an SPF value of 22.646 demonstrated an ultraprotection category of sunscreen activity.